Genetic Instability Promotes the Acquisition of Chromosomal Imbalances in T1b and T1c Breast Adenocarcinomas - Harald Blegen; B. Michael Ghadimi; Annukka Jauho; Anders Zetterberg; Elina Eriksson; Gert Auer; Thomas Ried (Analytical Cellular Pathology)
In order to evaluate biological and genetic properties of early breast carcinomas we analyzed microdissected tissue from 33 primary breast carcinomas stage T1b and T1c with respect to the nuclear DNA content, the expression pattern of Ki‐67, cyclin A, p27KIP1, p53 and p21WAF1, and chromosomal gains and losses. The results show that T1b carcinomas (6–10 mm, n=17) were frequently near‐diploid (53%) with low proliferative activity and staining patterns of p53 and p21WAF1 that suggest the presence of wild type protein. The majority (12/16) of the T1c tumors (11–20 mm), however, was aneuploid, and proliferative activity and p53 expression were increased. Larger tumor size correlated with an increasing number of chromosomal copy number changes and in particular with regional amplifications. High level copy number increases (amplifications), however, were found exclusively in the aneuploid tumors. Amplification events correlated with elevated cyclin A and reduced p27 expression, respectively. Our results suggest that the sequential acquisition of genomic imbalances during tumor progression is accelerated in aneuploid tumors, and may contribute to the increased malignancy potential.